2018
DOI: 10.5009/gnl17489
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Recombinant Soluble Thrombomodulin for Disseminated Intravascular Coagulation Associated with Severe Acute Cholangitis

Abstract: Background/AimsRecently, recombinant human soluble thrombomodulin (rTM) has been developed as a new drug for disseminated intravascular coagulation (DIC). This study aims to evaluate the clinical benefit of rTM in patients with sepsis-induced DIC caused by acute cholangitis who underwent biliary drainage.MethodsPatients were divided into two groups: the rTM therapy group and the non-rTM therapy group. The primary outcome was the DIC resolution rate at 7 days, and the secondary outcome was 28-day mortality rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
6
0
4
Order By: Relevance
“…In previous reports dealing with DIC resolution and treatment outcomes of DIC, different and controversial results were shown because of differences in the patients' background characteristics [9,18]. The present study identified three important points by analyzing DIC resolution and survival or DIC non-resolution and nonsurvival according to the organ failure, as follows.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In previous reports dealing with DIC resolution and treatment outcomes of DIC, different and controversial results were shown because of differences in the patients' background characteristics [9,18]. The present study identified three important points by analyzing DIC resolution and survival or DIC non-resolution and nonsurvival according to the organ failure, as follows.…”
Section: Discussionmentioning
confidence: 86%
“…With respect to DIC resolution, Okuda et al reported that DIC resolution in patients treated with TM-α was related to a better outcome of DIC [18]. In contrast, Saito et al reported that higher DIC resolution in patients treated with TM-α was not significantly related to the outcome of DIC [9].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Preliminary evidence suggests a limited impact of the underlying cause of sepsis, although data have been inconsistent. [25][26][27][28] In an observational study of 1787 patients with sepsis-associated DIC, 28day survival rates were 66.4%, 48.5%, and 31.1% when rhsTM was started respectively on the same day, 4 days, and more than 7 days after DIC diagnosis. These observations suggest potentially larger survival benefits if rhsTM is started early after the diagnosis of the coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the presence of SAC, other factors such as the underlying cause of sepsis or timing of rhsTM administration have been evaluated for their potential influence on treatment efficacy. Preliminary evidence suggests a limited impact of the underlying cause of sepsis, although data have been inconsistent 25‐28 . In an observational study of 1787 patients with sepsis‐associated DIC, 28‐day survival rates were 66.4%, 48.5%, and 31.1% when rhsTM was started respectively on the same day, 4 days, and more than 7 days after DIC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclastogenesis was also observed in macrophages derived from myeloid TM deleted mice, suggesting an anti-inflammatory role for TM in circulating cells [37]. Use of recombinant TM protein improves the survival of DIC patients [64] and attenuates the inflammatory bone loss in collagen antibody-induced arthritis and ovariectomy-induced mice models [37]. Apart from these direct effects, TM mediated generation of APC has been shown to reduce LPS-induced secretion of TNFα, IL-1β, IL-6, and IL-8 from human monocytes and THP-1 cell line [65].…”
Section: Thrombomodulin and Mapk Signaling In Leukocytesmentioning
confidence: 99%